2022
DOI: 10.3389/fpls.2021.785589
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Differences in Covariation Among Root Traits Across Plant Growth Forms, Mycorrhizal Types, and Biomes

Abstract: Fine roots play an important role in plant ecological strategies, adaptation to environmental constraints, and ecosystem functions. Covariation among root traits influence the physiological and ecological processes of plants and ecosystems. Root trait covariation in multiple dimensions at the global scale has been broadly discussed. How fine-root traits covary at the regional scale and whether the covariation is generalizable across plant growth forms, mycorrhizal types, and biomes are largely unknown. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
2
3
0
Order By: Relevance
“…Since WUE was not correlated with water use but was positively correlated with shoot weight, it could be that root traits that improve nutrient absorption to synthesize more shoot dry matter might be positively correlated with WUE. Our results are supported by previous reports on the multifaceted role of fine roots in plant resource acquisition, net primary production, and adaptation to environmental changes (An et al., 2022; Diaz et al., 2004; McCormack et al., 2014, 2015). According to the root economics spectrum (RES) hypothesis, roots with an acquisitive strategy are characterized by a thin diameter (i.e., fine roots) (An et al., 2022).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since WUE was not correlated with water use but was positively correlated with shoot weight, it could be that root traits that improve nutrient absorption to synthesize more shoot dry matter might be positively correlated with WUE. Our results are supported by previous reports on the multifaceted role of fine roots in plant resource acquisition, net primary production, and adaptation to environmental changes (An et al., 2022; Diaz et al., 2004; McCormack et al., 2014, 2015). According to the root economics spectrum (RES) hypothesis, roots with an acquisitive strategy are characterized by a thin diameter (i.e., fine roots) (An et al., 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are supported by previous reports on the multifaceted role of fine roots in plant resource acquisition, net primary production, and adaptation to environmental changes (An et al., 2022; Diaz et al., 2004; McCormack et al., 2014, 2015). According to the root economics spectrum (RES) hypothesis, roots with an acquisitive strategy are characterized by a thin diameter (i.e., fine roots) (An et al., 2022). Taken together, our results emphasize the importance of fine roots in enhancing the WUE of cotton.…”
Section: Discussionsupporting
confidence: 92%
“…More details of these traits can be seen in Table S2. Previous studies have found that RCN was closely related to root tissue density (RTD) at both the species and community level (Wang et al ., 2018; An et al ., 2022). Therefore, to analogize with leaf traits, we considered RCN here instead of RTD, even which is the more commonly used RES trait.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, only plants with arbuscular mycorrhizal associations were examined in this study due to the tropical woody plants are dominated by arbuscular mycorrhizal species [54,55]. However, root resource acquisition strategies are also influenced by mycorrhizal type [23,56]. Mycorrhizal type can impact the relationships between fine root chemical (e.g., RNC) or morphological (e.g., SRL) traits and root respiration [57].…”
Section: Tropical Plant Root Traits Followed a Multidimensional Patte...mentioning
confidence: 99%
“…How root systems impact plant growth and ecosystem processes is closely tied to the interplay among fine root chemical, morphological, and physiological traits [3]. Although root respiration shapes nutrient acquisition and plays a vital role in the RES [18,19], previous studies testing the RES hypothesis predominantly focused only on chemical and morphological traits, given the relative difficulty of measuring respiration [20][21][22][23]. But there are also several studies in grassland, temperate forest, and subtropical forest ecosystems that incorporate root respiration into the RES.…”
Section: Introductionmentioning
confidence: 99%